Characterization of electrosprayed chitosan/PLA-PEG-PLA (copolymer) nanoparticles for encapsulation of hydrophilic drug - Hien, Nguyen Thi Thanh; Phu, Huynh Dai; Anh, Ha Cam; Long, Huynh Bao; Trinh, Tong Ngoc (Vietnam Journal of Science and Technology, 2022)
Hydrophilic drug encapsulation efficiency of nanoparticles has recently received attention from the field of medicine delivery. In this work, chitosan/PLA-PEG-PLA copolymer (CS/CP) nanoparticles containing paracetamol were produced by an electrospraying method. Interactions between functional groups of chitosan, the copolymer, and the drug in their structures were demonstrated by Fourier-transform infrared spectroscopy (FTIR) and X-ray powder diffraction (XRD). The morphology and size of the nanoparticles formed at different ratios of CS/CP were evaluated by scanning electron microscopy (SEM). As a result of the optimal conditions, the obtained CS/CP-drug nanoparticles were spherical shapes with average diameters of around 220 nm. Importantly, the nanoparticles possessed a good encapsulation efficiency of 60.25 %. These studies suggest that electrosprayed nanoparticles become compact by linkages between the active sites of the material and hydrophilic drugs, and that can significantly improve the encapsulation of therapeutic molecules.